Withaferin A Acts as a Novel Regulator of Liver X Receptor-α in HCC - Shiragannavar, Varsha D.; Gowda, Nirmala G. Sannappa; Kumar, Divya P.; Mirshahi, Faridoddin; Santhekadur, Prasanna K. (Frontiers in Oncology, 2021)
Withaferin A, a steroidal lactone derived from the Withania somnifera plant has been known for its anti-cancerous effects on various types of cancer cells. However, its effect on the hallmarks of cancer such as proliferation, migration, invasion, and angiogenesis is still poorly understood. The antitumor property of Withaferin A and its molecular mechanism of action on hepatocellular carcinoma (HCC) cells is not yet completely established. In this study, we aimed to elucidate the novel molecular function of Withaferin A on HCC cells and its effect on various gene expression. Our results clearly showed that Withaferin A treatment to HCC cells inhibited proliferation, migration, invasion, and anchorage-independent growth. Further, we explored the Withaferin A target genes by blotting human angiogenesis, and cytokine arrays using conditioned media of Withaferin A treated QGY-7703 cells. We found that many of Nuclear factor kappa B (NF-ҡB), angiogenesis and inflammation associated proteins secretion is downregulated upon Withaferin A treatment. Interestingly, all these genes expression is also negatively regulated by nuclear receptor Liver X receptor- α (LXR-α). Here, we explored a novel mechanism that Withaferin-A activated LXR-α inhibits NF-ҡB transcriptional activity and suppressed the proliferation, migration, invasion, and anchorage-independent growth of these HCC cells. All these data strongly confirmed that Withaferin A is a potent anticancer compound and suppresses various angiogenesis and inflammatory markers which are associated with the development and progression of HCC. This beneficial and potential therapeutic property of Withaferin A will be very useful for the treatment of HCC.